Histomorphology of Thyroid Gland in Surti Goats (Capra hircus) - R. Menaka, (Indian Journal of Veterinary Anatomy, 2022)
The present study was conducted on the thyroid glands of 30 Surti goats of three different postnatal agegroups. The capsule of the thyroid gland was well distinguished by three layered as outer, middle and inner layer.The distinct layer differentiation was due to the amount of fat deposition which determined the thickness of thethyroid capsule. The connective tissue comprised of predominantly collagen fibers with few reticular fibers. . Thetrabeculae penetrated in to the glandular area and terminated with narrow tapering end in the centre of the thyroidgland. . The thyroid follicles were lined with simple low cuboidal and simple high cuboidal epithelium. Thesimple low cuboidal epithelium was observed while storing the colloidal substance in the thyroid follicles atresting stage. The simple high cuboidal epithelial lining was observed during the active stage of the thyroidfollicles. The varying sizes of the follicles were observed the large and small follicles were dominantly seenthroughout the glandular area. The parafollicular cells either arranged singly or in groups. The C cells werelocated in the interfollicular space with lightly stained cytoplasm and large spherical nucleus.